2010
DOI: 10.1037/h0100470
|View full text |Cite
|
Sign up to set email alerts
|

Seven case studies of individuals expelled from positive-only programs.

Abstract: In the debate over aversives a little-known but significant fact is often overlooked: programs that restrict themselves to positive-only treatment procedures sometimes expel individuals with severe behaviors when their behaviors become too difficult to handle. We review seven such cases of individuals with severe behavior problems who were exp elled from state-of-the-art, positive-only programs and describe what happened to them when they were enrolled in a program that was able to supplement its positive-only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In addition, very few studies collected information on whether CESS was acceptable to those implementing or overseeing the treatment (e.g., families, staff). Finally, as with Duker et al (2002), several studies included other treatments in combination with CESS (e.g., differential reinforcement of other behavior, physical guidance, verbal reprimands, functional communication training), making it difficult to evaluate the isolated effects of CESS on behavior change (e.g., Israel et al, 2008Israel et al, , 2010Williams et al, 1994;Williams, Kirkpatrick-Sanchez, & Iwata, 1993).…”
Section: Methodological Concernsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, very few studies collected information on whether CESS was acceptable to those implementing or overseeing the treatment (e.g., families, staff). Finally, as with Duker et al (2002), several studies included other treatments in combination with CESS (e.g., differential reinforcement of other behavior, physical guidance, verbal reprimands, functional communication training), making it difficult to evaluate the isolated effects of CESS on behavior change (e.g., Israel et al, 2008Israel et al, , 2010Williams et al, 1994;Williams, Kirkpatrick-Sanchez, & Iwata, 1993).…”
Section: Methodological Concernsmentioning
confidence: 99%
“…The extant CESS literature provides inconsistent information regarding the immediate and long-term effectiveness of CESS, as well as whether treatment gains were maintained once CESS was removed. Regarding the immediacy of effectiveness, several studies (e.g., Linscheid, Iwata, Ricketts, Williams, & Griffin, 1990;Salvy, Mulick, Butter, Bartlett, & Linscheid, 2004) demonstrated that CESS significantly reduced challenging behavior in only a few brief sessions (e.g., 10 min), whereas other studies demonstrated that CESS was only effective after numerous months of all-day implementation (e.g., Israel et al, 2008Israel et al, , 2010. Regarding long-term efficacy, some studies showed that CESS remained effective for many months (e.g., Mudford, Boundy, & Murray, 1995;Williams et al, 1993), while other studies showed that CESS lost its effectiveness over longer periods of time (e.g., Ricketts, Goza, & Matese, 1993).…”
Section: Difficulties With Long-term Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations